(untitled) (Biological Sciences - PJSIR, 2005)
Reinvestigation of the aerial parts of Adhatoda vasica led to the isolation of a new triterpenoid, 3a-hydroxy- oleanane-5-ene (1). The structure of this compound was elucidated and identified by spectral studies.